2014
DOI: 10.1007/s10464-014-9640-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Neighborhood Social Capital Buffer the Effects of Maternal Depression on Adolescent Behavior Problems?

Abstract: Neighborhood characteristics have been shown to impact child well-being. However, it remains unclear how these factors combine with family characteristics to influence child development. The current study helps develop that understanding by investigating how neighborhoods directly impact child and adolescent behavior problems as well as moderate the influence of family characteristics on behavior. Using multilevel linear models, we examined the relationship among neighborhood conditions (poverty and social cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 69 publications
(88 reference statements)
0
31
1
Order By: Relevance
“…No consensus currently exists on whether the effects of neighborhoods are stronger for younger or older young people. Although some studies (Sastry & Pebley, 2010;Woolley et al, 2008) indicated stronger neighborhood effects for older children, others (e.g., Delany-Brumsey et al, 2014) found that neighborhoods exerted greater influence on children than on adolescents. Our finding of a smaller effect size in adolescents than in children may be due to other unmeasured aspects of living in disadvantaged neighborhoods, such as exposure to neighborhood violence or deviant peer associations, than to socioeconomic disadvantage per se.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…No consensus currently exists on whether the effects of neighborhoods are stronger for younger or older young people. Although some studies (Sastry & Pebley, 2010;Woolley et al, 2008) indicated stronger neighborhood effects for older children, others (e.g., Delany-Brumsey et al, 2014) found that neighborhoods exerted greater influence on children than on adolescents. Our finding of a smaller effect size in adolescents than in children may be due to other unmeasured aspects of living in disadvantaged neighborhoods, such as exposure to neighborhood violence or deviant peer associations, than to socioeconomic disadvantage per se.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we conducted a systematic review and meta-analysis for the remaining 43 articles. We derived 49 effect sizes for the metaanalysis because five studies (Drukker, Kaplan, Feron, Van Os, & Korebrits, 2010;Fagan & Wright, 2012;Heberle, Thomas, Wagmiller, Briggs-Gowan, & Carter, 2014;Karriker-Jaffe, Foshee, Ennett, & Suchindran, 2009;Pabayo, Molnar, & Kawachi, 2014) reported results separately for male and female participants, and one study (Delany-Brumsey, Mays, & Cochran, 2014) reported results separately for children (ages 5-11 years) and adolescents (ages 12-17 years). Two studies (Goodnight et al, 2012;Santiago, Wadsworth, & Stump, 2011) reported the neighborhood effects on both aggression and delinquency, and one study (Farrell, Mehari, Kramer-Kuhn, & Goncy, 2014) reported outcomes across two time points; thus, we used the combined effects across outcomes and time points.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Scarce resources and supports, community violence, vandalism and crime, substance use and the accessibility of drugs, unstable housing, unemployment, and food insecurity (Slopen, Fitzmaurice, Williams, & Gilman, 2010) contribute to high rates of caregiver stress and depression in poverty-impacted communities (Delaney-Brumsey, Mays, & Cochran, 2014). Additionally, poverty undermines the parent/child relationship and erodes the quality of parenting, which, along with environmental stressors, elevates the risk of child behavioral problems (Burke, Loeber, & Birmaher, 2002; Delany-Brumsey et al, 2014; Sundquist et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They are naturally embedded within a community context, and are therefore intricately related to other contextual risks. Cumulative risk exposure across multiple ecological domains significantly increases risk for maladaptive outcomes (Stoddard et al 2013; Farmer et al 2004; Chilenski and Greenberg 2009); however, at the same time, exposure to protective or promotive factors in one domain may attenuate the effects of risk in the other (Delany-Brumsey et al 2014). This suggests that families and the communities in which they reside are related in nuanced and complex ways (Delany-Brumsey et al 2014).…”
Section: Introductionmentioning
confidence: 99%